Community composition of the Planctomycetes associated with different macroalgae. Issue 3 (2nd June 2014) - Bondoso, Joana; Balagué, Vanessa; Gasol, Josep M.; Lage, Olga M.
Abstract: Insights into the diversity of marine natural microbial biofilms, as for example those developing at the surface of marine macroalgae, can be obtained by using molecular techniques based on 16S rRNA genes. We applied denaturing gradient gel electrophoresis (DGGE) with 16S rRNA genes–specific primers for Planctomycetes to compare the communities of these organisms developing on six different macroalgae ( Chondrus crispus, Fucus spiralis, Mastocarpus stellatus, Porphyra dioica, Sargassum muticum, and Ulva sp.) sampled in spring 2012 in two rocky beaches in the north of Portugal. Planctomycetes can be one of the dominant organisms found in the epibacterial community of macroalgae, and we wanted to determine the degree of specificity and the spatial variation of these group. Shannon diversity indexes obtained from the comparison of DGGE profiles were similar in all the macroalgae, and in both sites, F. spiralis was the algae presenting lower Planctomycetes diversity, while M. stellatus and P. dioica from Porto showed the highest diversity. The analysis of DGGE profiles, including anosim statistics, indicate the existence of a specific Planctomycetes community associated with the algal host, likely independent of geographical variation. Sequencing of DGGE bands indicated that Planctomycetes communities were highly diverse, and some Operational Taxonomic Units seemed to be specifically associated with each macroalgae. Abstract : DGGE fingerprinting profile of the planctomycetes epiphytic communities in macroalgae and corresponding dendrogram evidencing the host-specificity of these communities.